Factors limiting the distribution of the mycoheterotrophic plants in fragmented landscape - Kotilínek, Milan (Jihočeská univerzita, 2021)
This thesis investigates the influence of habitat, dispersal abilities and evolution on distribution of mycoheterotrophic plants represented by six orchid species. Several methods including seed trapping, in situ seed germination, fungal barcoding, gene flow study and stable isotopes analyses were used to examine this topic. The final synthesis of these approaches shows lower limitation by dispersal abilities and stronger limitation by habitat.
Factors limiting the distribution of the mycoheterotrophic plants in fragmented landscape
Keywords: germination; mixotrophy; orchid mycorrhiza; Orchidaceae; dispersal limitation; habitat limitation; habitat occupancy; fragmented landscape; gene flow; microsatellite DNA markers; seed dispersal; seed traps; next generation sequencing; fungal barcoding; germination; mixotrophy; orchid mycorrhiza; Orchidaceae; dispersal limitation; habitat limitation; habitat occupancy; fragmented landscape; gene flow; microsatellite DNA markers; seed dispersal; seed traps; next generation sequencing; fungal barcoding